PENGARUH PERTUMBUHAN PENJUALAN, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE2016-2021 - Anggraeni, Rini; Syafe'i, Darman; ., Muznah; ., Epriyanti (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2024)
The main objective of this research was to determine the influence of sales growth, accounts receivable turnover, and inventory turnover on profitability in food and beverage companies listed on the Indonesia Stock Exchange (BEI). From all listed food and beverage companies, there were 30 companies, but determined using the purposive sampling method so that only 7 companies for the period 2016-2021 were obtained. The method used was panel data regression. From the analysis results, the regression equation showed Yit= -6.103093 + 0.075242 X1+ 0.599779 X2+ 2.060479 X3. The results of the research showed that partially, sales growth was known that the value of thitung < ttabelor 1.104451 <1.68595, the decision was Ho was accepted and Ha was rejected. It meant that Sales Growth (X1) did not have a significant influence on Profitability. Theresults of the research showed that partially, accounts receivable turnover was known that the value of thitung< ttabelor 1.029582< 1.68595, the decision was Ho was accepted and Ha was rejected, which meant that accounts receivableturnover (X2) did not have a significant influence on Profitability and the results of the research showed that partially, inventory turnover could be known that the value of thitung> ttabelor 2.083648 > 1.68595, the decision was Ho was rejected and Ha was accepted, whichmeantthatInventory Turnover(X3)hadasignificant influence on profitability. From the results of the Determination Coefficient (Adjusted R-squared), it showed that the ability of sales growth, accounts receivable turnover, and inventory turnover variables in explaining the variation of the profitability variable (return on asset) was 0.146822 or 14.7%, while the remaining 85.3% was influenced by other variables not explained and researched in the research model that is like cash turnover, working capital turnover, and liquidity. In the profitability variabel, other measurements can be used such as Net Profit Margin, Gross Profit Margin, Return On Equity and Return On Investment.